A New Advanced Topology for Photo Voltaic Applications - Sreedhar M; C. K. Panigrahi; Abhijit Dasgupta; J. Pati (Institute of Advanced Engineering and Science, 2015)
This article proposes a high efficient DC-DC step-up converter with a single switch. This is particularly suited for Photo Voltaic (PV) applications, automotive applications, battery operated vehicles etc., in which voltage is step up from 10V to 500V. This converter operates at 100 kHz due to which switching losses are comparatively high. This topology proposes a scheme to mitigate power losses across the switch and to achieve high efficiency by Zero Current Switching (ZCS) at “Turn ON and Turn OFF” states. Proposed converter uses a single switch to reduce the losses in the converter and observed 98% of overall efficiency in the converter. The proposed converter is verified by its experimental results.